The study of the mineralogical composition and flotation parameters of quartz-graphitized schist - Babakhanova, Zebo; Aripova, Mastura; Khodjaev, Nodir; Khamidov, Renat (Publishing House of Lviv Polytechnic National University, 2016)
Exploration studies in Uzbekistan revealed one graphite deposit (Taskazgan) and about 25 sites with varying perspective degree. In order to obtain the graphite for refractory industry uses insufficiently known Rupat, Zauchak and Zahchahona sites were studied. According to the research, Zahchahona site can be classified as a medium-sized field; the refined graphite content in the ore deposit is 3 to 15 %, which meets the requirements of the industry for this type of raw material. Graphite was refined by flotation and leaching process, brought to grade of 75 % carbon. Показано, що за даними геологорозвідки в Узбекистані існує один графітовий поклад (Taskazgan) і близько 25 ділянок різної перспективи. Проведені дослідження нових покладів Rupat, Zauchak і Zahchahona для одержання графіту для вогнетривкої промисловості. Визначено, що поклад Zahchahona може бути класифікований як середній за розміром; вміст очищеного графіту в родовищі руди становить від 3 до 15 %, що відповідає вимогам галузі для даного виду сировини. Проведено очищення графіту флотацією та вилуговуванням, що привело до вмісту вуглецю 75 %.
Дослідження мінералогічного складу та флотаційних параметрів кварц-графітового сланцю
Keywords: graphite; crystalline schist; concentrate; flotation; графіт; кристалічний сланець; концентрат; флотація